US pivot toward India after 9/11 : from a dubious relationship to a strategic partnership - Sarker, Masud (Lanham : Lexington Books, 2023)
"The author's argument is that the US policy toward India is more one of continuity than change. The driving force behind recent Indo-US relations is not primarily the consequences of 9/11 but is rather the result of power shifts within a more globalized world where 9/11 provided an additional conducive environment"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: United States -- Foreign relations -- India; India -- Foreign relations -- United States; United States -- Strategic aspects; India -- Strategic aspects; United States -- Foreign relations -- 21st century; India -- Foreign relations -- 21st century